Evaluation of the effect of a hyperbranched polyester on the thermal, rheological, morphological and mechanical properties of polyvinyl chloride/hemp fiber blends (2019)
The aim of this study was to investigate the effect of the hyperbranched polyester polyol from second generation content on the structural, thermal, rheological, morphological and mechanical properties of recycled polyvinyl chloride/hemp fiber/hyperbranched polyester polyol obtained from second generation blends. In all blends, the amounts of recycled polyvinyl chloride and hemp fiber were 70 wt% and 30 wt% respectively. The blends were obtained in a torque rheometer. The proportions of hyperbranched polyester polyol regards to those of the polyvinyl chloride and hemp fibers were 5 wt%, 10 wt%, 15 wt% and 20 wt%. Additionally, a recycled polyvinyl chloride/hemp fiber blend was prepared to be used as control blend. Infrared analysis was then used to evidence the interaction between components of the blends. The thermal stability of the recycled polyvinyl chloride/hemp fiber/hyperbranched polyester polyol blends was lower than that of the polyvinyl chloride. Furthermore, it was not observed a trend in the thermal behavior of the recycled polyvinyl chloride blends. Hyperbranched polyester polyol increased the glass transition temperature of the blends. Additionally, rheological analysis results indicated that the hyperbranched polyester polyol reduced the viscosity of the blends.